DISSENT AND HUMAN RIGHTS IN CHINA (Journal of the Spanish Institute for Strategic Studies, 2018)
Abstract The Chinese government still considers the massacre that occurred on the 4th of June 1989 a taboo subject and rejects the petitions of the victims’ families, especially the petition presented by the NGO ‘Mothers of Tiananmen’, to investigate the military intervention in Beijing’s central square that aimed to bring nearly two months of student protests to an end.